Penentuan Rute Terpendek Pendistribusian Galon Menggunakan Metode VRP (Vehicle Routing Problem) PT. ABC - Kabul, Putri Meiliawati; Fitriani, Risma; Arifin, Jauhari; Damayanti, Atika (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2025)
Most people have switched to using bottled drinking water that is consumed compared to PDAM water that is cooked by themselves. Therefore, the determination of the shortest route for the distribution of bottled drinking water delivery (AMDK) to the last distribution route is carried out. Determination of the shortest route taken in carrying out distribution is carried out because there are often vacancies at agents caused by delays in delivery by the depot so that in this case the distribution of bottled drinking water becomes very crucial in fulfilling public demand for bottled drinking water needs. Delays in distribution from the depot can be caused by a lack of efficiency in the delivery path so that several obstacles are encountered during the process. Therefore, the shortest route optimisation will be carried out for the efficiency of distribution time which aims to increase customer satisfaction related to product availability in accordance with the demand submitted by the community which is expected to have a smooth distribution path that will impact on the timeliness of product arrival using the Vehicle Routing Problem (VRP) method. Where this method is used in a distribution system to create an optimal route. Based on the results of determining three preferred routes, for determining the distribution route from Kasomalang to the final destination, Garut, the second route was selected as the shortest route determined by